Bone Marrow-Derived Mesenchymal Stem Cells Improve Diabetic Neuropathy by Direct Modulation of Both Angiogenesis and Myelination in Peripheral Nerves. Issue 2 (February 2016) - Han, Ji Woong; Choi, Dabin; Lee, Min Young; Huh, Yang Hoon; Yoon, Young-Sup
Recent evidence has suggested that diabetic neuropathy (DN) is pathophysiologically related to both impaired angiogenesis and a deficiency of neurotrophic factors in the nerves. It is widely known that vascular and neural growths are intimately associated. Mesenchymal stem cells (MSCs) promote angiogenesis in ischemic diseases and have neuroprotective effects, particularly on Schwann cells. Accordingly, we investigated whether DN could be improved by local transplantation of MSCs by augmenting angiogenesis and neural regeneration such as remyelination. In sciatic nerves of streptozotocin (STZ)-induced diabetic rats, motor and sensory nerve conduction velocities (NCVs) and capillary density were reduced, and axonal atrophy and demyelination were observed. After injection of bone marrow-derived MSCs (BM-MSCs) into hindlimb muscles, NCVs were restored to near-normal levels. Histological examination demonstrated that injected MSCs were preferentially and durably engrafted in the sciatic nerves, and a portion of the engrafted MSCs were distinctively localized close to vasa nervora of sciatic nerves. Furthermore, vasa nervora increased in density, and the ultrastructure of myelinated fibers in nerves was observed to be restored. Real-time RT-PCR experiments showed that gene expression of multiple factors involved in angiogenesis, neural function, and myelination were increased in the MSC-injected nerves. These findings suggest that MSC transplantation improved DN through direct peripheral nerve angiogenesis, neurotrophic effects, and restoration of myelination.